INVIOLABILITY OF THE HOME. POLICE SECURITY MEASURES. POLICE VIDEO DOCUMENTATION OF THE EXECUTION OF A SEARCH WARRANT AND ASSUMPTIONS IN RELATION TO THE VALIDITY OF POSSIBLE SPONTANEOUS STATEMENTS - Reyes López, Javier Ignacio (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2023)
The purpose of this doctrinal article is to analyse the latest trends regarding the concept of the place of residence in the field of investigative measures, specifically search warrants, and the specific comparison of the legal framework between the current Code of Criminal Procedure and the preliminary draft of the Code of Criminal Procedure. We will also analyse the peripheral security measures, the so-called "security fence" prior to the execution of a search warrant, and finally, a number of simultaneous measures in relation to the police video documentation of this procedure, in which spontaneous statements by suspects can be captured.